False‐negative rate of ultrasound‐guided fine‐needle aspiration cytology for identifying axillary lymph node metastasis in breast cancer patients. Issue 5 (13th June 2019) - Kane, Gavin; Fleming, Christina; Heneghan, Helen; McCartan, Damian; James, Philip; Trueick, Robert; Harrington, Luke; Nally, Fionn; Quinn, Cecily; O'Doherty, Ann; McNally, Sorcha; Rothwell, Jane; et al.
Abstract: Axillary nodal status remains an important determinant of prognosis and of the therapeutic strategy in patients with a newly diagnosed breast cancer. The aim of this study was to assess the false‐negative rate of ultrasound (US)‐guided fine‐needle aspiration cytology (FNAC) in axillary node staging at breast cancer diagnosis. All patients with a newly diagnosed breast cancer who had an indeterminate or suspicious axillary node sampled with an FNAC between 2007 and 2014 were included in the study. FNAC results were compared to the final histopathological results of surgically removed axillary lymph nodes. Patient demographics, tumor, and nodal characteristics were analyzed. Diagnostic accuracy tests were performed using IBM SPSS, version 22. A total of 3515 patients with breast cancer were identified, 675 of whom had ultrasound‐guided FNAC of ipsilateral axillary lymph nodes (mean age: 55 years; Range: 26‐84). A benign (C2) result was observed in 52% (n = 351) and a malignant (C5) result in 35% (n = 238). C1 was obtained in 11% (n = 76), C3 in 0.6% (n = 4), and C4 in 0.9% (n = 6). Of the 238 patients with a malignant (C5) FNAC, 99.6% had confirmed axillary lymph node metastatic disease on histopathology. Of the 351 patients with benign FNAC (C2), 31% (n = 108) of patients had a positive lymph node on histology. The false‐negative rate of preoperative FNAC remains too high (31%) to omit definitive surgical staging of the axilla. The high diagnostic accuracy when a positive FNAC is obtained allows appropriate tailored decisions regarding definitive therapy.